Real-world safety of PCSK9 inhibitors: A pharmacovigilance study based on spontaneous reports in FAERS - Feng, Zhen; Li, Xiaoye; Tong, Wai Kei; He, Qingfeng; Zhu, Xiao; Xiang, Xiaoqiang; Tang, Zhijia (Frontiers in Pharmacology, 2022)
Objective We aimed to evaluate alirocumab- and evolocumab-related adverse events (AEs) in real-world compared with all other drugs, overall and by gender and age subgroups; we also aimed to compare their risks of cognitive impairment, musculoskeletal disorders and diabetes with various statins and ezetimibe. Methods We retrospectively extracted AE reports from the FDA Adverse Event Reporting System (FAERS) database during July 2015-June 2021. Disproportionality analyses were performed using reporting odds ratios (RORs) to detect AE signals of alirocumab and evolocumab in the overall population and in different age and gender subgroups, respectively. Results Compared with all other drugs, both alirocumab and evolocumab had a significant signal in “musculoskeletal and connective tissue disorders” (ROR1 = 2.626, 95% CI 2.552-2.702; ROR2 = 2.575, 95% CI 2.538-2.613). The highest ROR value of 2.311 (95% CI 2.272-2.351) was for “injury, poisoning and procedural complications” and was found in patients aged ≥65 years on evolocumab. The most frequent AEs were “general disorders and administration site conditions” and “musculoskeletal and connective tissue disorders” for all subpopulations. At the preferred term level, the most frequent AE signal was myalgia for alirocumab and injection site pain for evolocumab, overall and by subgroups. Compared with statins/ezetimibe, PCSK9 inhibitors exhibited lower ROR values for adverse events associated with SOC “nervous system disorders”, “psychiatric disorders” and “metabolism and nutrition disorders” (all RORs <1), but mixed results for musculoskeletal disorders. Compared with all other drugs, undocumented AEs, such as acute cardiac event (ROR = 30.0, 95% CI 9.4-95.3) and xanthoma (ROR = 9.3, 95% CI 3.4-25.5), were also reported. Conclusions Real-world evidence showed that PCSK9 inhibitors were associated with an increased risk of musculoskeletal and connective tissue disorders and general disorders and administration site conditions, overall and by subgroups. Muscle toxicity, injection site reactions, and influenza-like illness were significant AE signals. Compared with various statins and ezetimibe, PCSK9 inhibitors have shown a favorable safety profile in muscle-related events, cognitive impairment and diabetes. Some undocumented AE signals were also reported. Due to the limitations of spontaneous reporting databases, further studies are still needed to establish causality and validate our results.